2012
DOI: 10.1177/147470491201000510
|View full text |Cite
|
Sign up to set email alerts
|

Applying Evolutionary Psychology to a Serious Game about Children's Interpersonal Conflict

Abstract: This article describes the use of evolutionary psychology to inform the design of a serious computer game aimed at improving 9-12-year-old children's conflict resolution skills. The design of the game will include dynamic narrative generation and emotional tagging, and there is a strong evolutionary rationale for the effect of both of these on conflict resolution. Gender differences will also be taken into consideration in designing the game. In interview research in schools in three countries (Greece, Portuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Conversely, Kollar et al (1991) indicated that males were more likely to suppress their feelings whereas females experienced more anger than males (Ghanizadeh, 2008;Alaka Mani et al, 2016) and tended to express their anger outwardly by pouting, sulking, and/or sharing about their feelings. Similar to the past research which stated that boys were less likely to describe their feelings (Ingram, Hondrou, Vasalou, Martinho, & Joinson, 2012), the male participants in this study displayed less anger than they experienced. Perhaps they were being socialized or conditioned to expect negative consequences (e.g., being rejected from peer group) for expressing anger outwardly which violated the normalized display rules (Kerr & Schneider, 2008).…”
Section: Advances In Social Science Education and Humanities Researcsupporting
confidence: 72%
“…Conversely, Kollar et al (1991) indicated that males were more likely to suppress their feelings whereas females experienced more anger than males (Ghanizadeh, 2008;Alaka Mani et al, 2016) and tended to express their anger outwardly by pouting, sulking, and/or sharing about their feelings. Similar to the past research which stated that boys were less likely to describe their feelings (Ingram, Hondrou, Vasalou, Martinho, & Joinson, 2012), the male participants in this study displayed less anger than they experienced. Perhaps they were being socialized or conditioned to expect negative consequences (e.g., being rejected from peer group) for expressing anger outwardly which violated the normalized display rules (Kerr & Schneider, 2008).…”
Section: Advances In Social Science Education and Humanities Researcsupporting
confidence: 72%
“…For example, similar negotiation occurs every time we bargain for a price with a seller or when we ask someone to make concessions uncertain of what the other is willing to give [25]. In previous research [22], we verified that children deal with similar issues on the playground. The paradigm is be same, although the the object of dispute changes.…”
Section: Discussionmentioning
confidence: 80%
“…The paper of Ingram et al (2012) is very fascinating and thought-provoking. The above-mentioned comments are intended to provide an additional source of inspiration for future research.…”
Section: Gender Differences In Human Interpersonal Conflictsmentioning
confidence: 99%
“…Females are supposed to be less directly aggressive than males, because direct aggression is considered inappropriate behavior for the feminine gender role. This may also explain another result of the Ingram et al study (2012). Girls were less likely to talk about responding to conflict with physical aggression, and talked more about feeling sad about the conflict and about conflicts in friendships.…”
mentioning
confidence: 99%
See 1 more Smart Citation